Modification of Ceramic Surfaces by Excimer Laser Processing - Becker, Wolfgang; Hutfless, Joachim; Geiger, Manfred (Cleo/Europe 94 Conference Proceedings, 1994)
Excimer laser radiation was found to be applicable in modifying ceramic surfaces. This technique proves to be novel, flexible and effective alternative to traditional modes of surface finishing of ceramics with costly diamond equipment. In this study, a XeCl excimer laser was applied to smooth alumina and silicon carbide ceramics. Basic testings were carried out to obtain data with regard to interaction mechanisms and to determine the optical processing parameters. Meanwhile, strength and wear experiments are designated to characterize the mechanical and tribological features of the processed surfaces.
LFT Import::2019-08-05 (631)